UNDERSTANDING TAX NON-COMPLIANCE INTENTION AMONG SME OWNERS IN MALAYSIA: DENIAL OF RESPONSIBILITY IMPACT AS MODERATOR - Nor Zuhairatun Md Radzi; Zaimah Zainol Ariffin, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Small and medium enterprises (SMEs) are pivotal to Malaysia's economic framework, significantly contributing to national income. However, tax non-compliance among SME owners remains a subject of ongoing debate. Addressing this issue requires consideration beyond the economic perspective, encompassing non-economic views as well. This study seeks to empirically extend the Theory of Planned Behaviour (TPB) by incorporating the concept of neutralisation techniques to evaluate the relationships between TPB constructs, denial of responsibility and tax non-compliance intention. Additionally, it investigates the moderating effect of denial of responsibility. A survey was conducted, distributing questionnaires randomly to 580 SME owners in Malaysia, resulting in a 72.8 percent response rate. Data were analysed using the PLS-SEM statistical tool. The findings indicate that attitude towards tax non-compliance and subjective norms significantly and positively influence tax non-compliance intention, whereas perceived behavioural control shows a negative influence. Furthermore, the positive relationship between subjective norms and tax non-compliance intention weakens when SME owners employ the denial of responsibility technique. These results offer significant theoretical and practical implications, providing valuable insights for academicians, policymakers, and tax authorities in formulating strategies to address tax non-compliance among SME owners. Suggestions for future research are also highlighted.